Clinical outcome of colposcopy guided biopsy in women with abnormal Pap smear results - Baranwal, Nilakshi; Sharma, Rupali; Rachna; Agarwal, Megha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Cervical cancer is the fourth most common cancer among women globally and remains a significant public health challenge despite being largely preventable. Persistent infection with high-risk human papillomavirus (HPV), particularly HPV-16 and HPV-18, is the primary cause. Early detection through effective screening methods, such as Pap smear and colposcopy, plays a critical role in reducing cervical cancer incidence. This study evaluates the clinical outcomes of colposcopy-guided biopsy in women with abnormal Pap smear results, highlighting the importance of integrated screening approaches. Methods: This prospective observational study was conducted in the department of obstetrics and gynaecology, GS medical college and hospital, Hapur, over 15-18 months (November 2022-February 2024). A total of 150 women aged 25-65 years with abnormal Pap smear results and cervical symptoms (e.g., leukorrhea, postcoital bleeding, intermenstrual bleeding) were included. Colposcopy-guided biopsies were performed on these patients. Data were analysed using IBM SPSS version 27, applying statistical tests like the T-test and chi-square test, with p<0.05 considered significant. Descriptive statistics summarized the data, presented in charts and tables. Results: Among the 150 participants, 10.6% had abnormal Pap smear findings, and 17.3% had abnormal colposcopy findings. Squamous metaplasia (46.15%) and high-grade lesions (34.61%) were the most frequently observed abnormalities during colposcopy, while Pap smears predominantly revealed ASC-US (56.25%) and HSIL (31.25%). Postcoital and postmenopausal bleeding had the highest rates of abnormal findings. Colposcopy demonstrated greater sensitivity compared to Pap smear in detecting cervical lesions, emphasizing its importance in early diagnosis. Conclusions: Colposcopy is more sensitive than Pap smear in detecting cervical abnormalities, particularly high-grade lesions. Combining these methods enhances the accuracy and reliability of cervical cancer detection. Integrating molecular tests and visual inspection techniques into existing screening protocols could further improve outcomes. Raising public awareness about regular screening, HPV vaccination, and early detection is essential to reducing cervical cancer burden globally.